Optimalisasi Keterampilan Akuntansi untuk Meningkatkan Nilai Tambah Mahasiswa di Dunia Kerja - Pertiwi, Dwi Ari; Agustina, Rachma; Ardiana, Meta; Rosyadi, M. Syam'un; Musfiroh, Anita; Widoyoningrum, Sri; Rodliyah, Iesyah (ABIDUMASY, 2024)
The Merdeka Belajar Kampus Merdeka policy prepares students to participate in the global economy by encouraging them to learn about various topics outside of their area of competence (Ulum et al., 2023). From the analysis of the partner's situation, the problem faced by partners or the Sharia Economic Law Study Program, namely students of the Sharia Economic Law Study Program, Faculty of Islamic Religion, Hasyim Asy'ari University Tebuireng Jombang, is that the problem of students of the Sharia Economic Law study program is not getting accounting courses so that Students have no knowledge of accounting, whether basic accounting, service company accounting, and preparing financial reports, while one of the profiles of graduates from the Sharia Economic Law study program is to become an accountant, so training is very necessary to increase accounting knowledge. Keywords: Competitiveness, Accounting Skills